2021
DOI: 10.1038/s41598-021-87289-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 11 SARS-CoV-2 antibody tests by using samples from patients with defined IgG antibody titers

Abstract: We evaluated the performance of 11 SARS-CoV-2 antibody tests using a reference set of heat-inactivated samples from 278 unexposed persons and 258 COVID-19 patients, some of whom contributed serial samples. The reference set included samples with a variation in SARS-CoV-2 IgG antibody titers, as determined by an in-house immunofluorescence assay (IFA). The five evaluated rapid diagnostic tests had a specificity of 99.0% and a sensitivity that ranged from 56.3 to 81.6% and decreased with low IFA IgG titers. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…The decision to carry out an LFIC test as a front-line testing assay was made to restrict venipuncture to those returning negative results by LFIC, given the extreme frailty of many recruited residents. Although LFIC are designed to be interpreted qualitatively (positive/negative result), in line with a previous report [ 9 ], we showed that the intensity of IgG test line reactivity increased in parallel to antibody levels measured by the Roche ECLIA, which in turn strongly correlate with neutralizing antibody titers [ 13 , 14 ]. Using this semiquantitative approach, we observed that the antibody response elicited by the vaccine appeared stronger over time and more durable in SARS-CoV-2-recovered than in naïve nursing home residents, in line with previous findings [ 6 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The decision to carry out an LFIC test as a front-line testing assay was made to restrict venipuncture to those returning negative results by LFIC, given the extreme frailty of many recruited residents. Although LFIC are designed to be interpreted qualitatively (positive/negative result), in line with a previous report [ 9 ], we showed that the intensity of IgG test line reactivity increased in parallel to antibody levels measured by the Roche ECLIA, which in turn strongly correlate with neutralizing antibody titers [ 13 , 14 ]. Using this semiquantitative approach, we observed that the antibody response elicited by the vaccine appeared stronger over time and more durable in SARS-CoV-2-recovered than in naïve nursing home residents, in line with previous findings [ 6 ].…”
Section: Discussionsupporting
confidence: 87%
“…No pre-vaccination specimens were available for analyses. The OnSite COVID-19 IgG/IgM Rapid Test (CTK BIOTECH, Poway, CA, USA), a lateral flow immunochromatographic assay (LFIC) for detection of anti-SARS-CoV-2-S IgG and IgM antibodies with an specificity of 99% [ 9 ] was used for the purpose. Specifically, this LFIC detects antibodies binding to the subunit 1 (S1) of the S protein, which contains a receptor-binding domain that recognizes and binds to the host receptor angiotensin-converting enzyme 2.…”
Section: Methodsmentioning
confidence: 99%
“…As we had to use two different tests, though from the same manufacturer and with similar performance characteristics, error in the prevalence estimate could have occurred. The lower sensitivity of rapid diagnostic tests and in low titre samples 16 and the measurement of the IgM and IgG only could also have led to the underestimation of prevalence. Selection bias limited our ability to infer to the source population, and memory bias may have led to under-reporting of exposures particularly regarding symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Lagerqvist et al showed that the sensitivities of different serology assays decrease for low IgG titer samples. This is the case for samples from early post symptom onset, in the late convalescent phase, in asymptomatic or mild infections, which are largely represented in our selection [ 23 ].…”
Section: Discussionmentioning
confidence: 99%